2003
DOI: 10.1002/ejlt.200390042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heating time and oxygen availability on lipid oxidation in meat emulsions

Abstract: The aim of the present study was to investigate the effect of heating time and oxygen availability on lipid oxidation during chill storage, using different step indicators, in a meat emulsion model. Lipid oxidation was measured by conjugated dienes, hydroperoxides and 2‐thiobarbituric acid reactive substances formation on raw and cooked meat emulsion at 80 °C in different oxygen availability bags, at 0 °C during 35 d. The results obtained showed that heat treatment and oxygen availability affected conjugated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…In line with previous studies (Andreo, Doval, Romero, & Judis, 2003;Ferioli, Caboni, & Dutta, 2008;Gray, Gomaa, & Buckley, 1996) highest MDA contents were found in meat that had been heat processed and then stored (Fig. 3).…”
Section: Tbars In Meat From Different Game Species As Affected By Emsupporting
confidence: 92%
“…In line with previous studies (Andreo, Doval, Romero, & Judis, 2003;Ferioli, Caboni, & Dutta, 2008;Gray, Gomaa, & Buckley, 1996) highest MDA contents were found in meat that had been heat processed and then stored (Fig. 3).…”
Section: Tbars In Meat From Different Game Species As Affected By Emsupporting
confidence: 92%
“…There have been lots of literature reports about MDA production in meat products during storage or cooking. Besides, MDA as the marker to evaluate the oxidation condition of vegetable oils was also reported by many researchers (Andreo et al ., ; Roux et al ., ; Papastergiadis et al ., ; Koh & Surh, ). But our preliminary experiment found that MDA content showed poor correlations with other oxidative indicators, such as peroxide value, acid value and p‐anisidine value, and probably could not be used to evaluate the oxidation of animal fat (lard and tallow) with low PUFA content (unpublished data).…”
Section: Introductionmentioning
confidence: 98%
“…But no kinetic data are available on the formation of MA (or TBARS) during cooking. A few studies provide kinetic data to characterize lipid oxidation products in meat either during storage or cooking [3,10,15,16] but no attempt has been made to model the process.…”
Section: Introductionmentioning
confidence: 99%